The Relation between Electronic Game Play and Executive Function among Preschoolers. - Yang, Xiaohui; Wang, Zhenhong; Qiu, Xiaoju; Zhu, Liqi (Journal of Child & Family Studies, 2020)
We examined the relation between electronic game play and executive function (EF) in Chinese preschoolers. One hundred and nineteen 3- to 6-year-old children participated. Children's working memory, inhibition, and planning were assessed as measures of EF development. Parents completed a questionnaire regarding children's electronic game play time and the game content. The results showed that time spent on electronic games (M = 0.30 h, SD = 0.41, ranging from 0 to 2.14 h per day) was positively related to EF when controlling for other relevant factors, such as children's age, gender, and socioeconomic status. However, action content in electronic games was negatively related to one inhibition aspect of EF, but not two other aspects, namely working memory and planning. The results of the present study indicate time spent using media is associated with EF development in children but that evidence for content-related issues is inconclusive. Highlights: Whether electronic games are beneficial or harmful to children is a matter of public debate. Children's working memory, inhibition, and planning were assessed as measures of executive function (EF). Time spent on electronic games was positively related to EF. Action game content was negatively but weakly correlated with inhibition, but not working memory or planning.